THE DIET OF SKIERS WITH REGARD TO THE FREQUENCY OF DINNERS - Vasilios Giovanis; Kiriakos Amoutzas; Efstathios Vasileiou; Efstathia Ramadani; Efthimios Badas (Physical Education of Students, 2013)
The aim of the present study is the assessment of the dietary habits of Greek alpine ski athletes, with regard to the consumption of specific food groups as well as the evaluation of their compliance with the official dietary recommendations of international organizations. The sample consisted of 65 Greek skiers, both experienced and inexperienced. Three groups of trainees participated: 1) a group of students of Athens, elective skiing –28 people, 2) a group of students of Athens, specialization skiing – 21 people, 3) group of experienced skiers - 16 people. The sample taking was based on the following criteria: a) the skiers had to be Greek, b) to be over 18 years old, c) the questionnaires had to be completed anonymously in their leisure time. The questionnaires were given to the participants, including the following subjects: frequency of daily dinners, daily intake of cereals – baked products, daily intake of dairy products, daily intake of animal protein, daily intake of seafood, daily intake of fatty food, daily intake of vegetables – juice – fruit and daily intake of sweets. Taking into account the results, we are driven to the following conclusions: the update of information of skiers concerning the intake of wrong food is considered necessary. It is ascertained that the majority of people (83%) in all three groups (elective, specialization, experienced skiers) have 4-5 dinners daily. The majority of people in three groups have less than 3 servings daily: of animal protein, dairy products, vegetables, fruit and juice.